COMPARATIVE ANALYSIS OF YIELD AND QUALITY IN SUGARCANE GENOTYPES UNDER WATERLOGGED AND NORMAL CONDITION - NAVNIT KUMAR,; H. SINGH,; RINKI KUMARI,; V. P. SINGH, (The Bioscan, 2015)
A field experiment was conducted from 2009 - 10 to 2010 - 11 at Sugarcane Research Institute, Pusa, Bihar to evaluate 9 sugarcane genotypes for their yield and quality characteristics under waterlogged and normal condition. Among genotypes, BO 147 had significantly higher growth and yield attributes viz., germination (46.0 and 44.2 %), plant population (2, 15600 and 2, 05700/ ha), cane height (232.2 and 254.7 cm), cane diameter (2.06 and 2.23 cm), millable cane (1, 10800 and 1, 23600/ ha), single cane weight (705 and 785 g) and cane yield (76.5 and 91.4 t/ ha) in waterlogged and normal condition, respectively. The genotype CoLk 94184 showed the significantly higher values of brix (19.79 and 20.65 %) and pol per cent (17.48 and 18.47 %) respectively under waterlogged and normal conditions. But, maximum purity per cent (92.20 and 92.55 %) juice was obtained by BO 147. Significantly higher gross return (‘ 1, 56800 and 1, 87400/ ha), net return, (99,200 and 1, 26500/ ha) and benefit: cost ratio (2.72 and 3.08) was obtained by the genotype BO 147 under waterlogged and normal condition, respectively. This was closely followed by BO 146 which gave the net return of ‘79800 and 1, 00600/ ha, respectively under waterlogged and normal situation. Overall, genotype BO 147 performed best among all other genotypes may be recommended for waterlogged condition to obtain good yield and economic return.